2009
DOI: 10.1111/j.1399-6576.2009.02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Infusion requirements and reversibility of rocuronium at the corrugator supercilii and adductor pollicis muscles

Abstract: A larger rocuronium infusion dose was required to maintain a constant neuromuscular block at the CSM. Neostigmine-mediated reversal was faster at the CSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The time from administration of rocuronium 1 mg/kg until T1 spontaneously reached 10% of the control value was markedly longer in our patient as compared to patients with normal neuromuscular function (70 min [7]). The time taken for T1 to reach 10% in our patient (112 min) was measured during intravenous anesthesia using propofol and remifentanil, while the previous data was observed during anesthesia with sevoflurane [7], which is known to significantly prolong the duration of action of rocuronium to 1.5–2 times [8, 9]. Assuming that the values observed in the other study were potentiated by sevoflurane, the time from administration of rocuronium 1 mg/kg to the recovery of T1 to 10% of the control level observed in our MD patient seems to have been roughly doubled.…”
Section: Discussionmentioning
confidence: 92%
“…The time from administration of rocuronium 1 mg/kg until T1 spontaneously reached 10% of the control value was markedly longer in our patient as compared to patients with normal neuromuscular function (70 min [7]). The time taken for T1 to reach 10% in our patient (112 min) was measured during intravenous anesthesia using propofol and remifentanil, while the previous data was observed during anesthesia with sevoflurane [7], which is known to significantly prolong the duration of action of rocuronium to 1.5–2 times [8, 9]. Assuming that the values observed in the other study were potentiated by sevoflurane, the time from administration of rocuronium 1 mg/kg to the recovery of T1 to 10% of the control level observed in our MD patient seems to have been roughly doubled.…”
Section: Discussionmentioning
confidence: 92%
“…The timing principle with rapid-onset rocuronium, on the other hand, enables the induction of general anesthesia shortly after an injection of rocuronium without the need to observe the patient's reaction. When higher-dose rocuronium is administered, the lag before detectable twitch depression is shortened to only about 30 s [18]. It is therefore recommended that hypnotic drugs should be injected 15-20 s after the administration of rocuronium, as done in the present study, to prevent patient discomfort.…”
Section: Discussionmentioning
confidence: 95%
“…This study is the first to investigate the response of the adductor muscles of the thigh to rocuronium. Many previous studies have reported differing responses of various muscles to rocuronium . The response to rocuronium is also known to vary between individual patients, and many factors (such as age, sex, body mass index, race, etc.)…”
Section: Discussionmentioning
confidence: 99%